Israel's First Physician and Apothecary Noah and the Origins of Medicine in the Book of Jubilees - Syfox, Chontel (2018)
The book of Jubilees paints Noah as the first physician and apothecary, who received knowledge of natural medicine from the angels of God so that he could save his offspring from the ailments being inflicted upon them by evil spirits. This article examines this aspect of the Noah tradition in the book of Jubilees and attempts to identify its origins. The study considers the potential textual and ideological impetuses behind this tradition, and proposes that attributing the beginning of medical knowledge to Noah may have served to create a licit category of medicine for the author of Jubilees' intended audience.
Keywords: Jubilees; Noah; Second Temple Judaism; Disease; Healing; Medicine